INFLUENCE OF CROP SPATIAL VARIABILITY WHEN CALCULATING IRRIGATION NETWORK FLOWS1. (30th January 2013) - Monserrat, J.; Ezpeleta, M.; Colomer, M.A.; Cots, LL.; Barragan, J.
ABSTRACT In on‐demand irrigation network design, calculation of pipe flows is usually based on the mean water requirements of the crops that can be expected to be planted in the area. However, while the network is sized for mean water needs, the actual requirements of each plot will depend on the crop planted and may well be different from the calculated mean water needs. As a result, the network may be undersized in terms of covering the flow demands of certain of its sections. The aim of this work was to study the influence of the spatial variability of crops on network flows and to make recommendations for methods of calculation capable of providing more reliable values for these flows. An equation was obtained that made it possible to determine what is known as the operation quality (OQ) based on the section number and the coefficient of variation of the water needs of the crops planned for the area. This equation was applied to two networks with different plot sizes and the results were compared with others obtained when the mean water requirements were assumed. Copyright © 2013 John Wiley & Sons, Ltd.